Heart rate response and technical demands of different small-sided game formats in young female basketballers - Sánchez-Sánchez, J.; Carretero, M.; Valiente, J.; Gonzalo-Skok, O.; Sampaio, J.; Casamichana, D. (Revista Internacional de Ciencias del Deporte, 2018)
The aim of the present study was to describe the physiological and technical responses in young female during a basketball 3 vs. 3 small-sided games (SSG) with and without verbal coach encouragement and dribbling. Six young female basketball players (age: 14.3 ± 0.5 years; height: 167.8 ± 0.8 cm; body mass: 56.5 ± 5.7 kg) were recruited to participate in the present pilot study. The games were video recorded and afterwards the technical demands were notated with observational ad hoc software. The peak of maximum heart rate was increased from set 1 to set 3 during both the SSG with dribble and coach encouragement, as well as in the SSG without dribble and coach presence. With coach encouragement caused greater responses of heart rate and rate of perceived exertion than without both dribble and coach encouragement. There were no differences in technical actions, exception of the number of offensive rebounds showing a higher number in the coach encouragement task. In conclusion, the SSG with verbal encouragement should be selected to focus in physiological load, and SSG without might be useful to enhance collective behavior, without limitations in physiological load.